Formulation of a peel-off gel mask containing mundu fruit extract (Garcinia dulcis (roxb.) kurz) for antioxidant and anti-elastase activity - Ambarwati, Neneng Siti Silfi; Desmiaty, Yesi; Chandra, Amelia; Noviani, Yuslia; Triyani, Yulia; Hakim, Ratu Mayra; Amanda, Reistha Fazlia; Wahyudi, Dion (Faculty of Pharmacy, Universitas Pancasila, 2025)
The skin serves as a protective barrier against ultraviolet (UV) radiation. However, exposure to UV radiation can lead to various skin problems, including changes in the dermis. To prevent UV-induced damage, antioxidants and anti-elastase agents are needed to protect the skin from oxidative stress. This study aims to evaluate the antioxidant and anti-elastase activities of Mundu fruit extract (Garcinia dulcis (Roxb.) Kurz) and to formulate a peel-off gel mask using the concentrated extract. Antioxidant activity was assessed using the FRAP and ABTS methods, while anti-elastase activity was determined by measuring the release of p-nitroaniline from a substrate degraded by the elastase enzyme. The results showed that the IC50 value for antioxidant activity using the ABTS method is 29.57 ppm 0.72, and the FRAP value was 185.02 10.23 AAE/g. The anti-elastase activity showed IC50 of 82.21 ppm. Three peel-off gel mask formulations were developed, with Formula 3 (containing extract at 200 x IC50). showing the best performance. These findings suggest that the thick Mundu fruit extract, which tested positive for phenolic compounds, exhibits promising antioxidant and anti-elastase activities and is suitable for use in topical formulations.